Một Số Câu Hỏi Về Việc Dùng Các Cụm Từ "Đức Giêsu", "Đức Maria" - Nguyen, Hai Tinh (Khoa Học Công Giáo và Đời Sống, 2022)
The article takes as pre-text the discussion on the translation of the name Jesus to Vietnamese language to explore further issues in linguistics, Biblical exegesis and Christology. The exploration implements common knowledge in Bible study and theology to help elucidate the issues at stake which may be present in many other theological discussions in Vietnam. The article suggests that the traditional term "Chúa Giêsu" is more sound both in linguistic and theological senses than the recently formed term "Đức Giêsu". Bài viết này đặt ra một số vấn đề của việc dùng các cụm từ "Đức Giêsu", "Đức Maria" và gợi ý việc dùng lại các cụm từ có truyền thống lâu đời và còn được Giáo Hội Việt Nam chính thức dùng: "Chúa Giêsu", "Đức Chúa Giêsu", "Mẹ Maria", "Đức Mẹ", "Đức Mẹ Maria". Chúng tôi xin đi thẳng vào vấn đề.